2008
DOI: 10.1094/pdis-92-8-1247a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Iris yellow spot virus on Onion (Allium cepa) in Serbia

Abstract: Iris yellow spot virus (IYSV; genus Tospovirus, family Bunyaviridae) is established in several European countries (France, Italy, The Netherlands, Poland, Slovenia, Spain, and the UK) and its distribution in the EU region has increased since 2002 (3). In July 2007, symptoms resembling those of IYSV were observed in an onion (Allium cepa) seed crop in the Sirig locality in Serbia. Onion plants exhibited characteristic symptoms of chlorotic or necrotic spindle and diamond-shaped lesions on the leaves and scapes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Comparative evaluation of mechanical and thrips-transmission of IYSV indicated that only thrips-transmission was effective, and therefore was adopted further in the study. This is in line with the previous reports by Bulajić, 2008, Srinivasan et al (2010), and Naveed and Pappu (2012).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Comparative evaluation of mechanical and thrips-transmission of IYSV indicated that only thrips-transmission was effective, and therefore was adopted further in the study. This is in line with the previous reports by Bulajić, 2008, Srinivasan et al (2010), and Naveed and Pappu (2012).…”
Section: Discussionsupporting
confidence: 94%
“…Virus transmission using T. tabaci was adopted for this study because mechanical inoculation attempted as described was not successful and this was also reported previously (Bulajić, 2008; Srinivasan et al, 2010; Naveed and Pappu, 2012). A cohort of 500 first instar (≤ 8 h-old) T. tabaci obtained from icipe ’s insectary were allowed to acquire virus by feeding on IYSV-infected Allium cepa var.…”
Section: Methodsmentioning
confidence: 79%
“…There is no information on damage and economic impact, except that estimated incidence on onion was high in Slovenia (29) and that severely infected plants eventually died in Spain (11). However, most recent records of IYSV outbreak in several European countries such as Italy (7), Germany (5), the UK (33), and Serbia (9), and the virus occurrence in different areas of France on onion and shallot (22), as well as a new report on leek in Spain (10) could represent increasing incidence of IYSV in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, survey for the virus has been initiated only by several countries, and in almost all of them IYSV has been detected only sporadically and in restricted areas. In addition to the Netherlands and Israel, IYSV has been recorded in Slovenia (29), Italy (7,13), Poland (8), Spain (10,11), France (22,23), Germany (5,28), the UK (33), and Serbia (9).…”
mentioning
confidence: 99%
“…IYSV is a recently emerging tospovirus, with outbreaks in onions recorded from Spain (Cordoba-Selles et al, 2005), Germany (Leinhos et al, 2007), Greece (Chatzivassiliou et al, 2009), Italy (Tomassoli et al, 2009), Serbia (Bulajic et al, 2008), the Netherlands (Hoedjes et al, 2011) and the UK (Mumford et al, 2008). T. tabaci is the only reported vector of IYSV (Cortes et al, 1998;Kritzman et al, 2001), but recently F. fusca has been described as a second vector in the USA (Srinavasan et al, 2012).…”
Section: Occurrence Of Tospoviruses In the Risk Assessment Areamentioning
confidence: 99%